Tradisi Buwuh Pernikahan Di Desa Panjang Jiwo : Dalam Perspektif Hukum Islam - Husain, Muhammad Ilham Nur Hasan; Afif, Abdullah (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2024)
The Buwuh tradition in several areas has a different way of pronouncing it. Some Javanese people call it a nyumbang which aims to help neighbors who have needs. Although in the end it was returned when the buwuh had an intention. This is like the people of Panjang Jiwo Village, Tenggilis Mejoyo District, Surabaya City. This study aims to find out how the buwuh tradition is practiced in walimah al-ursy in the people of Panjang Jiwo Village and their views on Islamic law. This research is field research with descriptive analysis and data collection using observation, interviews and documentation. While the approach uses legal anthropology. The results of this study are that the buwuh tradition occurs because of the basic attitude of wanting to help the community, rising in the form of material or non-material. The custom that occurs in Panjang Jiwo Village, Surabaya City regarding buwuhan on walimatul 'ursy is 'urf which has become a habit. So that it is not contrary to Islamic law, because there is nothing that is detrimental and harmed.